2012
DOI: 10.1007/s12306-012-0189-0
|View full text |Cite
|
Sign up to set email alerts
|

The long head of biceps as a source of pain in active population: tenotomy or tenodesis? A comparison of 2 case series with isolated lesions

Abstract: The tendon of the long head of the biceps (LHB) is a common source of pain in the shoulder, and the surgical treatments proposed are tenotomy or tenodesis performed in different ways. The purpose of this study is to compare the clinical results (objective and subjective) of tenotomy versus soft tissue tenodesis. One-hundred and four patients with an isolated LHB pathology, arthroscopically treated between 2004 and 2007, were observed retrospectively. Forty-eight of these patients were treated with tenotomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 29 publications
3
64
0
2
Order By: Relevance
“…Sekiya et al presented a description of a percutaneous soft-tissue technique (PITT) and reported predictable pain relief, absence of cosmetic deformity, and good patient satisfaction in their 4-year experience using this technique [78]. Delle Rose et al, in a retrospective study of 56 patients who underwent arthroscopic soft tissue LHB tenodesis, reported a significant improvement in the clinical outcome scores (Constant score (48.9 to 84.9), VAS (8.8 to 1.4) and DASH score (55.8 to 11.4), and a failure rate of 5.3 % (3 cases)) [103].…”
Section: Clinical Outcomes After Arthroscopic Lhb Tenodesismentioning
confidence: 99%
“…Sekiya et al presented a description of a percutaneous soft-tissue technique (PITT) and reported predictable pain relief, absence of cosmetic deformity, and good patient satisfaction in their 4-year experience using this technique [78]. Delle Rose et al, in a retrospective study of 56 patients who underwent arthroscopic soft tissue LHB tenodesis, reported a significant improvement in the clinical outcome scores (Constant score (48.9 to 84.9), VAS (8.8 to 1.4) and DASH score (55.8 to 11.4), and a failure rate of 5.3 % (3 cases)) [103].…”
Section: Clinical Outcomes After Arthroscopic Lhb Tenodesismentioning
confidence: 99%
“…Due to the concern regarding increased rates of complications in older patients, some surgeons elect to perform only biceps tenotomies in these patients. The limited evidence in the literature, reports comparable outcomes for biceps tenodesis versus tenotomy [18][19][20][21][22][23], though studies show that patients treated with tenotomies have greater incidence of postoperative cramping and cosmetic deformity [18][19][20][21]23].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]15 The long head of the biceps tendon (LHBT) is an independent pain generator that is a frequent complaint in patients with shoulder pain. 3 There is a ''net-like pattern'' of sensory and sympathetic neural fibers concentrated at the tendon origin on the glenoid that is a major contributor to pain in the shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…3 There is a ''net-like pattern'' of sensory and sympathetic neural fibers concentrated at the tendon origin on the glenoid that is a major contributor to pain in the shoulder. 2 LHBT pathologies have recently become more commonly recognized in association with other pathologies of the shoulder. Ignoring LHBT pathology has been shown to lead to an inferior outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation